Calvin's New Testament commentaries ; vol. 11 - Calvin, John, 1509-1564; Parker, T.H.L.; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1965)
Contents : v. 11 : The epistle of Paul the Apostle to the Galations, Ephesians, Philippians and Colossians. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Galatians -- commentaries; Bible. N.T. Ephesians -- commentaries; Bible. N.T. Philippians -- commentaries; Bible. N.T. Colossians -- commentaries